Antibiotic susceptibility and REP-PCR fingerprints of Acinetobacter spp. isolated from a hospital ten years apart - Misbah, Suzana; AbuBakar, Sazaly; Hassan, Hamimah; Hanifah, Yasmin Abu; Yusof, Mohd Yasim Mohd (Elsevier, 2004)
The antibiotic susceptibility profiles and the repetitive extragenic palindromic sequence-based polymerase chain reaction (REP-PCR)-determined genotypes of 109 Acinetobacter strains collected from the University Malaya Medical Center (UMMC), Kuala Lumpur, Malaysia, in 1987 (N=21) and 1996-1998 (N=88) were established. Twelve antibiotic susceptibility profiles of antibiotics used at the UMMC were obtained. In descending order of effectiveness, imipenem, amikacin and ciprofloxacin were the most effective against the Acinetobacter strains. Compared with 1987 isolates, the isolates obtained in 1996-1998 had decreased susceptibility to these antibiotics and were tolerant to the antibiotics up to an MIC90 of greater than or equal to256 mg/L. REP-PCR DNA fingerprints of all the isolates revealed the presence of four Acinetobacter spp. lineages; 92 of all the isolates belonged to two dominant lineages (genotypes 1 and 4). Genotype 4 isolates predominant in 1987 showed increased resistance and antibiotic tolerance to imipenem, amikacin and ciprofloxacin compared with the 1996-1998 isolates. In contrast, genotype 1 isolates from 1996-1998 were mainly sensitive to these antibiotics. These findings demonstrate the presence of at least two independent Acinetobacter spp. lineages in the same hospital, and suggest the possibility that genotype 4 Acinetobacter spp. acquired the resistance phenotype in situ, whereas most of the genotype 1 isolates were probably introduced to the hospital in recent years. (C) 2004 The Hospital Infection Society. Published by Elsevier Ltd. All rights reserved.